Examining mental health literacy, help seeking behaviours, and mental health outcomes in UK university students - Denise Hill (The Journal of Mental Health Training, Education and Practice, 2017)
PurposeMany university students in the UK experience mental health problems and little is known about their overall mental health literacy and help-seeking behaviours. The purpose of this paper is to ascertain levels of mental health literacy in UK university students and to examine whether mental health literacy is associated with better mental health outcomes and intentions to seek professional care.Design/methodology/approachA total of 380 university students at a university in the south of England completed online surveys measuring multiple dimensions of mental health literacy, help-seeking behaviour, distress, and well-being.FindingsMental health literacy in the students sampled was lower than seen in previous research. Women exhibited higher levels of mental health literacy than men and postgraduate students scored higher than undergraduate students. Participants with previous mental health problems had higher levels of mental health literacy than those with no history of mental health problems. Individuals were most likely to want to seek support from a partner or family member and most participants indicated they would be able to access mental health information online. Mental health literacy was significantly positively correlated with help-seeking behaviour, but not significantly correlated with distress or well-being.Practical implicationsStrategies, such as anonymous online resources, should be designed to help UK university students become more knowledgeable about mental health and comfortable with seeking appropriate support.Originality/valueThis study is the first to examine multiple dimensions of mental health literacy in UK university students and compare it to help-seeking behaviour, distress, and well-being.